Association of the PGC-1α rs8192678 Variant with Microalbuminuria in Subjects with Type 2 Diabetes Mellitus. Issue 6 (21st May 2013) - Prior, Sarah L.; Clark, Amy R.; Jones, Danielle A.; Bain, Steve C.; Hurel, Steve J.; Humphries, Steve E.; Stephens, Jeffrey W.
Abstract : PPAR-γ co-activator-1α (PGC-1α) is a tissue-specific transcriptional co-activator involved in the regulation of antioxidant enzymes. The A-allele of the rs8192678 PGC-1 α} (G>A) gene variant has previously been associated with nephropathy in Korean and Indian-Asian type 2 diabetes mellitus (T2DM) samples. Our aim was to examine the association between this variant and urine albumin exccretion in European subjects with T2DM. Genotyping was performed on 583 European subjects with T2DM and examined in relation to urinary albumin, plasma oxidized-LDL and small dense-LDL percentage. We observed a significant association between genotype (GG/GA/AA) and urinary albumin (normoalbuminuria v micro/macroalbuminuria: 48.6/39.7/11.7% v 38.2/51.2/10.5%, p =0.02; for GG v GA/AA, p =0.01). The odds ratio for micro/macroalbuminuria in GA and AA subjects relative to GG were 1.70 [1.15–2.50], p =0.008 and 1.20 [0.66–2.16], p =0.56 respectively (for GA/AA v GG: 1.58 [95% CI: 1.09–2.27], p =0.02). There was a significant association between the A allele and a higher percentage of small dense-LDL particles (GG v GA v AA: 70.8 [58.01–81.06] % v 72.8 [56.18–81.19] % v 78.9 [67.16–85.33] %, p =0.03). In European subjects with T2DM the GA relative to the GG genotype is associated with a 70% increase in the risk of micro/microalbuminuria. Furthermore, homozygosity for the A-allele is also associated with a preponderance of small dense-LDL particles.